Therapy Management of Metabolic Disorder Comorbidity With Depression - Ren, Yu; Luo, Hua; Jiang, Zheng-Li (Frontiers in Psychology, 2021)
Depression is a common disease that seriously endangers the physical and mental health of human beings, and it often coexists with other metabolic disorders such as diabetes and cancer. There have been endless reports on the mechanism, prevention, and cure of comorbidity because of its high incidence and poor prognosis and the increased burden on the family and society. There may be a specific comorbid basis and causal relationship between depression and metabolic diseases. Depression in patients with metabolic disorders can be effectively alleviated through psychotherapy and medication. The timely and effective treatment of depression can significantly improve the quality of life of patients with metabolic disorders, reduce their psychological burden, and promote the effective treatment of metabolic diseases. This study reorganized the research progress on the management of metabolic disorder comorbidity with depression.